Global governance and the new wars the merging of development and security - Duffield, Mark R. (London Zed Books, 2001)
In this hugely influential book, originally published in 2001 but just as - if not more - relevant today, Mark Duffield shows how war has become an integral component of development discourse. Aid agencies have become increasingly involved in humanitarian assistance, conflict resolution and the social reconstruction of war-torn societies. Duffield explores the consequences of this growing merger of development and security, unravelling the nature of the new wars and the response of the international community, in particular the new systems of global governance that are emerging as a result.
Includes bibliographical references (p. 266-279) and index.
Keywords: War--Economic aspects--Developing countries